PERSONAL GARANSI DALAM PRODUK QARDUL HASAN DI KSPPS BMT SALAFIYAH SUKOREJO SITUBONDO - Subaidi Subaidi; Subyanto Subyanto (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2021)
Qardul Hasan financing is one of the excellent products in finance. It can help lower class society and Small and Medium Enterprises (SMEs) to develop their business. This main advantage is there is a payoff without any profit-sharing or profit margins. However, the borrower by his own volition can give the excess of the loan. To borrow Qardul Hasan financing, the customer must submit collateral to KSPPS BMT Salafiyah in the form of goods or a personal guarantee system. Personal guarantee in financing is an embodiment of financing without collateral, as well as the application of personal guarantee in Qardul Hasan financing in KSPPS BMT Salafiyah. In its realization, KSPPS BMT Salafiyah provides Qardul Hasan financing to customers with personal guarantees. It means guarantee is in the form of signature and or statement of the figure as community leaders which he or she is responsible for the given financing.